Dynamic analysis of business development of auditing firms: Case of the Republic of Serbia 2010-2020 - Aleksandra Radojević; Biljana Jovković; Predrag Dragičević (Economic Themes, 2022)
Auditing firms are very important for business decision-makers and they have a large impact on business development, due to issued reports and competent opinions contained in such reports. The purpose of this paper is to present, to professional public, the current condition and changes of business results achieved by active auditing firms in the Republic to Serbia over the period of eleven years. The goal of the paper is an objective assessment of the state of play and operations of active auditing firms, as well as a determination of business trends and monitoring of the results achieved in the audit services market. The paper analyzes the changes in individual balance sheet items and profitability indicators, that is their average growth during the eleven years. The results indicate that the members of the 'Big Four' had not acquired a leadership position in the market, observed according to the productivity indicators. Actually, the results indicate that the auditing firms with the largest growth of net results, in the observed period, are not the leaders according to the criterion of assets growth. At the same time, the firms with the greatest growth of business income in the observed period are not at the same time the most productive firms, measured by net result per employee. The results obtained in this paper contribute to the formation of a realistic view of the situation in the audit services market, as well as the perspectives and tendencies in the development of audit firms.
Keywords: M42; M41; M40; 330; Auditing firms; the 'Big Four'; auditing service market; productivity; profitability; net result